Cataract surgery in children: Controversies and practices - Shrestha, UD (Nepalese Journal of Ophthalmology, 2012)
Pediatric cataract is totally different from adult cataract. The objective of this review article is to describe the peculiarities of pediatric cataract and the controversies and practices in pediatric cataract surgery. The differences in the surgical technique are discussed in the article. There are lots of controversies regarding IOL implantation in children. The result of the review is that the pediatric cataract surgery should be performed in between 6-8 weeks of age. There is no contra-indication for IOL implantation. Surgeons can implant either polymethylmethacrylate (PMMA) or Acrysoft foldable IOL. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5866 NEPJOPH 2012; 4(1): 138-149